2012
DOI: 10.1002/j.0022-0337.2012.76.6.tb05315.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Educational Course at an Iranian Dental School on Students’ Knowledge of and Attitudes About HIV/AIDS

Abstract: This study investigated the effects of an educational program designed to improve the knowledge and attitudes of senior dental students in an Iranian dental school about caring for patients with HIV/AIDS. As part of an extramural program in community dentistry, a new educational program about HIV/AIDS was developed at Tehran University of Medical Sciences in 2009. The program consisted of two days' observation at the Consultation Center for Behavioral Diseases and a one-day workshop on infection control. A con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 27 publications
(38 reference statements)
1
13
0
Order By: Relevance
“…Introduction of an educational programme at an Iranian dental school targeting students' knowledge of HIV/AIDS proved beneficial. Upon conclusion of the programme, a significant increase in the average knowledge ( p = 0.001) and attitude ( p = 0.009) scores was observed, as almost all students (more than 96%) reported that they would comply with infection control in future practice. It has been consistently proven that educational programmes have a positive effect on participants' knowledge and attitudes towards HIV/AIDS and in strengthening their infection‐control practices.…”
Section: Discussionmentioning
confidence: 96%
“…Introduction of an educational programme at an Iranian dental school targeting students' knowledge of HIV/AIDS proved beneficial. Upon conclusion of the programme, a significant increase in the average knowledge ( p = 0.001) and attitude ( p = 0.009) scores was observed, as almost all students (more than 96%) reported that they would comply with infection control in future practice. It has been consistently proven that educational programmes have a positive effect on participants' knowledge and attitudes towards HIV/AIDS and in strengthening their infection‐control practices.…”
Section: Discussionmentioning
confidence: 96%
“…The questionnaire used in the present study consisted of five major domains: a) HIV-related knowledge; b) attitudes toward PLWH; c) motivation to practice safe-sex; d) skills to practice safe-sex (including 2 sub-domains: perceived difficulty of AIDS preventive behaviors, perceived effectiveness of AIDS preventive behaviors); and e) HIV-related behaviors. The items for each sub-scale had been extracted from a pool of items utilized in previous studies [12]- [16] or from surveys previously validated in research works published by other Persian speaking researchers [10] [17]- [20]. We carefully evaluated the primary pool of items and further assessed the five domains as explained below:…”
Section: Methodsmentioning
confidence: 99%
“…It advocates continual disruption of existing ideologies and structures, an approach that requires the critical thinking that is expected at higher education level (Elkana 2009 Situated in low prevalence countries, the focus tended to be on transmitting information relevant to the intended profession, and/or the reduction of stigma (Burr et al 2006;Rohn et al 2006) to increase empathy towards HIV positive people graduates may come into contact with during their work. Programmes that only transmitted information were not as successful as those that also required students to interact with HIV positive patients (Jafari, Yazdani, Khami, Mohammadi and Hajiabdolbaghi 2012;Seacat et al 2009). When lectures were supplemented by behavioural components (e.g., role plays) and clinical components (actually interacting with patients) the outcomes were more effective (Mak and Yui 2010;Williams et al 2006;Zaninovic et al 2013).…”
Section: And Aids Educationmentioning
confidence: 99%